2012
DOI: 10.1111/j.1463-1318.2011.02907.x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic resection compared with laparoscopic rectal resection for cancer: systematic review and meta‐analysis of short‐term outcome

Abstract: Robotic surgery for rectal cancer has a lower conversion rate and a similar operative time compared with laparoscopic surgery, with no difference in recovery, oncological and postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(170 citation statements)
references
References 59 publications
10
151
3
2
Order By: Relevance
“…Complete mesocolic excision along with lymphadenopathy has been shown to be associated with better oncologic outcomes [7]. [22,23]. None of the three studies found a statistically significant difference in the number of nodes extracted by the robot as compared to laparoscopic resection.…”
Section: Oncologic Outcomesmentioning
confidence: 70%
“…Complete mesocolic excision along with lymphadenopathy has been shown to be associated with better oncologic outcomes [7]. [22,23]. None of the three studies found a statistically significant difference in the number of nodes extracted by the robot as compared to laparoscopic resection.…”
Section: Oncologic Outcomesmentioning
confidence: 70%
“…Indeed, the literature has shown evidence of its merits for rectal resections in the male pelvis as well as mid-and low-rectal tumors. [11][12][13] Whether any of these benefits will outweigh the cost of robotic assisted surgery will be addressed in the RObotic versus LAparoscopic Resection for Rectal cancer (ROLARR) study.…”
Section: Technical Improvementsmentioning
confidence: 99%
“…Results from a series of robotic TME suggest that it may allow better preservation of urinary and sexual functions [64]. A meta-analysis of eight non randomised studies of robotic versus laparoscopic rectal excision suggested that the conversion rate to open surgery in the robotic group was significantly lower than that with a laparoscopic surgery [65]. There were no significant differences in operation time, length of hospital stay, time to resume regular diet, postoperative morbidity and mortality, or the oncological accuracy of resection.…”
Section: Management Of Early Rectal Cancer and The Malignant Polypmentioning
confidence: 99%